New Employment Actors: Developments from Australia - Gould, Anthony M. (Relations industrielles / Industrial Relations, 2009)
New Employment Actors: Developments from Australia, edited by Grant Michelson, Suzanne Jamieson and John Burgess, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employment policies; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z